The Preparation of Student Worksheets (LKPD) Based on Guided Inquiry on Straight Motion Material - Putri Zuhra; Elisa Elisa; A Halim (Universitas Syiah Kuala, 2019)
This study aims to produce products namely guided inquiry-based LKPD on straight-motion material, knowing that LKPD is feasible to be used as a tool to help students learn, and knowing teacher and student responses to guided inquiry-based LKPD. This research uses the Research and Development (R D) method with the ADDIE model. The research subjects were 2 expert lecturers to validate guided inquiry-based LKPD, 17 SMP Negeri 3 Lhoknga students, and 2 Physics teachers. Data collection techniques were obtained from teacher interviews, LKP validation sheets, through student questionnaires, and teacher questionnaires. The data analysis technique uses descriptive qualitative. The results of data analysis showed that guided inquiry-based LKPD validation on straight-motion material